Trade-offs: The value of understanding the consequences of choice - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2020)
ISDC leads various rigorous, science-based activities guided by the principle of independence to support the One CGIAR reform. The 2020 approved workplan focuses on delivering thought-leadership to the System on trade-off analysis and analytics, and how these can best serve in the research strategy and program modalities design.